2015
DOI: 10.1093/abbs/gmv070
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous cellulolytic enzyme systems in the longhorn beetle <italic>Mesosa myops</italic> (Insecta: Coleoptera) studied by transcriptomic analysis

Abstract: The Cerambycidae (longhorn beetle) is a large family of Coleoptera with xylophagous feeding habits. Cellulose digestion plays an important role in these wood-feeding insects. In this study, transcriptomic technology was used to obtain one glycoside hydrolase family 45 (GH45) cellulase and seven GH5 cellulases from Mesosa myops, a typical longhorn beetle. Analyses of expression dynamics and evolutionary relationships provided a complete description of the cellulolytic system. The expression dynamics related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…GH1 enzymes have broad catalytic and substrate specificities and function as β-xylosidases, β-glucuronidases, β-galactosidases, β-mannosidases or exo-β-1,4-glucanases, serving to hydrolyse substrates released from the hemicellulose matrix. CAZymes include > 40 GH45 cellulases and 4230 records of GH5, including the activities of enzymes like β-mannosidase (EC 3.2.1.25), chitosanase (EC 3.2.1.132), endo-β-1,4-glucanase (endocellulase, EC 3.2.1.4) and others [ 79 ]. Several Lamiinae longhorn beetles contain relatively large numbers of copies of GH5 cellulase [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…GH1 enzymes have broad catalytic and substrate specificities and function as β-xylosidases, β-glucuronidases, β-galactosidases, β-mannosidases or exo-β-1,4-glucanases, serving to hydrolyse substrates released from the hemicellulose matrix. CAZymes include > 40 GH45 cellulases and 4230 records of GH5, including the activities of enzymes like β-mannosidase (EC 3.2.1.25), chitosanase (EC 3.2.1.132), endo-β-1,4-glucanase (endocellulase, EC 3.2.1.4) and others [ 79 ]. Several Lamiinae longhorn beetles contain relatively large numbers of copies of GH5 cellulase [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that MaCel1 may be a new member of the insect cellulase gene and its catalytic properties should be further investigated. There are different types of cellulase in different types of insects [43]. The β-D-Glucosidase activity of the MaCel1 was higher than that of the M. alternatus digestive tract previously reported, which might be caused by the different test objects [25].…”
Section: Discussionmentioning
confidence: 94%
“…Two proteins were assigned to GH45, which exhibits endoglucanase activity [16]. The CAZymes include more than 40 GH45 cellulases, including the activities of different enzymes, such as β-mannosidase (EC 3.2.1.25), chitosanase (EC 3.2.1.132), endo-β-1,4-glucanase (endocellulase, EC 3.2.1.4) and others [20]. Eleven candidates were assigned to GH5, which exhibits endoglucanase activity [21].…”
Section: Resultsmentioning
confidence: 99%